Usaha Tani Sawi Hijau Di Kelompok Tani Tanuse Desa Sumberejo Kecamatan Batu Kota Batu - Marselinus Dafrino Conco; Asnah Asnah; Dwi Asnawi Nurhananto (Universitas Islam Kadiri, 2023)
Sumberejo Village is one of the villages in the city of Batu, where most of the people work as farmers, and one of the villages that has the potential to produce mustard greens, and other horticultural crops. This study aims to analyze the production costs of Green Sawi farming in Sumberejo Village, Batu District. This research was conducted in Sumberejo Village, Batu District, Batu City, East Java, one of the villages that has the potential to produce green mustard and other horticultural crops. This research will be conducted in July 2022. Determination of the sample from the population is determined using the Random Sampling method, meaning that the method of determining the sample that will provide the opportunity for each member of the population to be selected is simple random. Darmawati, Munjin, Goris Seran (2015). The data analysis method used in this study to determine the cost of farming includes cost calculation, revenue calculation, and income calculation. Calculation of costs is a calculation carried out by the company which includes: labor costs, the amount of production costs. The variables used in this study are: Farming Business Costs, Green Mustard Farming, Total Costs, Fixed Costs, Variable Costs, Farming Business Revenues, Farming Business Profits and Revune Cost Ratio (R/C). Based on the results and discussion described above, it can be concluded that the production obtained from mustard green farming in the Tanuse farmer group, Sumberejo Village, is 9,933.35 kg/ha. Total Revenue of Rp. 79,466,833.3 per hectare. Total Income is Rp. 62.456,628.76 per hectare. The R/C ratio obtained is 1.27. The value > 1, it can be concluded that the mustard green farming in the Tanuse farmer group, Sumberejo Village, Batu City for 1 (one) planting season in this study can be said to be profitable and feasible to cultivate.